2013
DOI: 10.1007/s00027-013-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Resource partitioning among cladocerans in a littoral macrophyte zone: implications for the transfer of essential compounds

Abstract: International audienceThe maintenance of species diversity in a given environment is strongly linked to resource partitioning. Littoral macrophyte zones are heterogeneous environments with high microcrustacean diversity, where zooplankton have dietary access to seston as well as organisms growing on macrophytic surfaces (epiphyton). We conducted a field study in a macrophyte-rich backwater of the river Allier to examine how seston and epiphyton were used as potential food sources by four dominant cladoceran sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Throughout the summer stratification period, the δ 13 C Daphnia values were very close to the δ 13 C seston values in all four lakes studied. The slight differences found between the signatures of Daphnia and seston (averaging 0.4‰ during the summer stratification period) are similar to those already reported in the literature (del Giorgio & France, 1996; Grey et al, 2000; Masclaux et al, 2014; Morlock et al, 2017; Schilder et al, 2017). At that time of the year, seston is mainly composed of phytoplankton, and it is likely that most of the carbon assimilated by Daphnia comes from phytoplankton during this period, even if we cannot totally exclude other food sources.…”
Section: Discussionsupporting
confidence: 89%
“…Throughout the summer stratification period, the δ 13 C Daphnia values were very close to the δ 13 C seston values in all four lakes studied. The slight differences found between the signatures of Daphnia and seston (averaging 0.4‰ during the summer stratification period) are similar to those already reported in the literature (del Giorgio & France, 1996; Grey et al, 2000; Masclaux et al, 2014; Morlock et al, 2017; Schilder et al, 2017). At that time of the year, seston is mainly composed of phytoplankton, and it is likely that most of the carbon assimilated by Daphnia comes from phytoplankton during this period, even if we cannot totally exclude other food sources.…”
Section: Discussionsupporting
confidence: 89%
“…These relationships did not completely align with other studies (e.g., [ 31 , 33 , 34 ]), but this inconsistency may be explained by a single, important diet item in the fishes collected. Chydorids are benthic-oriented microcrustaceans that feed primarily on epiphyton [ 49 , 50 ]. Chydorids and other benthic invertebrates may serve as EPA-rich prey items to fish [ 31 , 33 ], and EPA is thought to be an important fatty acid for zooplankton growth and fitness [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue is the nutritional quality of zooplankton in littoral and pelagic areas as that is the key factor sustaining larval growth. Masclaux et al (2014) assessed the fatty acid composition of epiphyton and seston in the macrophyte rich littoral zone. They found that the epiphyton that can possibly provide an important dietary source for cladocerans in the littoral had higher content of nutritionally essential compounds of poly unsaturated fatty acids (PUFA) compared to the seston.…”
Section: Littoral As Food-rich Nursery For Perch Larvaementioning
confidence: 99%